2014
DOI: 10.1016/j.cmet.2014.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Control of Metazoan Heme Homeostasis by a Conserved Multidrug Resistance Protein

Abstract: Several lines of evidence predict that specific pathways must exist in metazoans for the escorted movement of heme, an essential but cytotoxic iron-containing organic ring, within and between cells and tissues, but these pathways remain obscure. In Caenorhabditis elegans, embryonic development is inextricably dependent on both maternally-derived heme and environmentally-acquired heme. Here, we show that the multidrug resistance protein, MRP-5/ABCC5, likely acts as a heme exporter and targeted depletion of mrp-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 50 publications
4
92
0
Order By: Relevance
“…Mutant rde-1 worms are resistant to RNAi, but restoring tissue-specific expression of the wild-type rde-1 cDNA in these mutants confers RNAi sensitivity to a specific tissue (27). We depleted cua-1 in wildtype N2, WM27 (rde-1 mutant, RNAi insensitive), VP303 (P nhx-2 ::RDE-1, intestine only RNAi), WM118 (P myo-3 ::RDE-1, muscle only RNAi), and NR222 (P lin-26 ::RDE-1, hypodermis only RNAi) worm strains (13). Knockdown of cua-1 in the intestine resulted in reduced fecundity similar to that of wholebody RNAi (Fig.…”
Section: Cua-1 Expression Is Regulated By Dietarymentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant rde-1 worms are resistant to RNAi, but restoring tissue-specific expression of the wild-type rde-1 cDNA in these mutants confers RNAi sensitivity to a specific tissue (27). We depleted cua-1 in wildtype N2, WM27 (rde-1 mutant, RNAi insensitive), VP303 (P nhx-2 ::RDE-1, intestine only RNAi), WM118 (P myo-3 ::RDE-1, muscle only RNAi), and NR222 (P lin-26 ::RDE-1, hypodermis only RNAi) worm strains (13). Knockdown of cua-1 in the intestine resulted in reduced fecundity similar to that of wholebody RNAi (Fig.…”
Section: Cua-1 Expression Is Regulated By Dietarymentioning
confidence: 99%
“…For these reasons, we utilized C. elegans, which has been widely used in the study of the metabolism of other metals, including iron, heme, and zinc (8,(13)(14)(15)(16)(17). Although mammals have two copper exporters, serving complementary functions in different tissues such as the gut and liver, lower metazoans (including nematodes (C. elegans) and insects (Drosophila melanogaster)) have only a single homolog of ATP7A/B (2,18,19).…”
mentioning
confidence: 99%
“…Korolnek et al [73] identified the multidrug resistance protein MRP-5/ABCC5 as another heme exporter in animals. In C. elegans, MRP-5 localizes to the basolateral surface of the intestinal cells and mediates heme export out of the intestine.…”
Section: Heme Exportmentioning
confidence: 99%
“…In C. elegans, MRP-5 localizes to the basolateral surface of the intestinal cells and mediates heme export out of the intestine. Deletion of mrp-5 results in embryonic death, which is due to impaired heme transfer to extra-intestinal tissues [73]. In vertebrate cells, MRP-5 localizes to both plasma membrane and intracellular compartments [73].…”
Section: Heme Exportmentioning
confidence: 99%
See 1 more Smart Citation